How the Use of Force against Non-state Actors Transformed the Law of Self-defence after 9/11 - Ozubide, Alabo (South African Yearbook of International Law, 2020)
<span style="color: #0a0a0a; font-family: Helvetica, Arial, sans-serif; font-size: 12px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #fefefe; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">In spite of the general ban on the use of force by states, there are threats to the integrity of the international system. these threats come mainly from transnational terrorist organisations (nSAs),1 the proliferation of weapons of mass destruction (wMD)2 and the growth of failed states. the idea is that these nSAs may acquire and launch these wMD from the territories of failed states, hence the three threats are linked.